The Influence of Service Quality and Customer Satisfaction on Consumer Loyalty at PT. Hajjah Fatimah Indo Group Bantaeng Regency - Multasamsi; Buyung Romadhoni; Sherry Edelia Natrir Kalla (GoodWill, 2024)
This study investigates the influence of service quality and customer satisfaction on consumer loyalty at PT. Hajjah Fatimah Indo Group in Bantaeng Regency, Indonesia. In the era of intense market competition, retail businesses must prioritize both service quality and customer satisfaction to retain consumers and enhance loyalty. A quantitative descriptive method was employed, with data collected through structured questionnaires distributed to 153 customers selected using purposive sampling. Service quality was measured using five dimensions: reliability, responsiveness, assurance, empathy, and tangibles, while customer satisfaction was assessed based on feedback systems, surveys, and transactional experiences. Consumer loyalty was evaluated through repeat purchases, positive recommendations, and brand preference. Data were analyzed using multiple linear regression in SPSS 25, with validity, reliability, and classical assumption tests conducted to ensure data quality. The results indicate that service quality significantly affects consumer loyalty (t = 3.561, p < 0.05), and customer satisfaction also has a significant positive effect on loyalty (t = 4.360, p < 0.05). Simultaneous testing confirms that service quality and customer satisfaction jointly influence consumer loyalty (F = …, p < 0.05), explaining 33.2% of its variance. The findings emphasize the critical role of high service standards and satisfaction-focused strategies in enhancing customer loyalty. This study provides actionable insights for retail managers seeking to strengthen consumer relationships, improve service delivery, and sustain competitive advantage in the growing Indonesian retail sector.